Platelets in Atherothrombosis: New and Evolving Roles - Weyrich, Andy; Cipollone, Francesco; Mezzetti, Andrea; Zimmerman, Guy (Current Pharmaceutical Design, 2007)
The functional interplay of platelets with leukocytes and endothelial cells is critical both in physiological conditions, such as host defense, wound repair and tissue healing, and in pathological conditions, such as thrombotic and inflammatory diseases. The understanding of the specific molecular links underlying these cellular interactions and the functional changes that they induce could suggest new targets for pharmacological intervention. In this review, we summarize some of the newly-recognized aspects of interaction between platelets and monocytes, neutrophils and endothelial cells, that are relevant to all of the phases of atherosclerosis progression, since the early steps of atherogenesis to plaque rupture and thrombosis, the main causes of acute coronary syndromes.
Keywords: RANTES